Directing mosquito - Wong, King Lam (Nanyang Technological University, 2020)
A filial fresh graduate brings home his first paycheck but comes to realize that his parents are hungry for his money and more. A darkly horrific twist on contemporary family dramas and the values of filial piety in Singapore, MOSQUITO asks - what happens when your parents want to suck your blood - literally? After earning his first paycheck, Jared comes home to his adoring parents and a night of celebration. However his parents start to change, with Ma's demands of him becoming increasingly intensive and intrusive, while his Pa develops a strange obsessive taste for sweet drinks and more. As the night approaches, Jared realises his parents are mutating into another species and has to make a terrible choice between obedience or survival